Analisis Perlindungan Hukum Terhadap Kepemilikan Hak Atas Tanah Bagi Kepentingan Umum - Julianti Sembiring; Ramsul Nababan; Putri Juliani Br Tarigan; Octa Vioni Pinem; Rizal Sanusi Hasibuan (Jurnal Relasi Publik, 2024)
This research aims to analyze legal protection for ownership of land rights for the public interest, and this research can be useful as a reference for readers. This research uses a qualitative descriptive research method, with a type of normative legal research - empirical or literature. Sugiyono said that quantitative research is a method used to examine the condition of natural objects where the researcher is the key instrument. type of normative-empirical legal research according to Muhaimin in his book entitled: Legal Research Methods says that normative-empirical legal research is "legal research that examines law as rules or norms and the application of legal rules in practice in society". The results found are that the existence of regulations regarding land acquisition provides a legal basis for the government to obtain land for the implementation of development in the public interest and is a guarantee for land rights holders to obtain adequate compensation, thereby providing better survival at a higher level of socio-economic life. prior to land acquisition. Land acquisition for development in the public interest is a land acquisition activity carried out by the government for the construction of public facilities. Land procurement consists of planning, preparation and implementation stages which involve the regional government as the executor of land acquisition, the ministry that carries out land affairs, land rights owners and affected communities.